Trojan multilateralism: Global cooperation in health - Devi Lalita Sridhar; Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2013)
This paper argues that recent global health cooperation has been marked by two trends. First, there has been a highly successful proliferation of vertical funds to fight specific diseases. These are characterised by narrower problem-based mandates; multistakeholder governance; voluntary and discretionary funding; no in-country presence for the delivery of assistance; and an output-based legitimacy (based on effectiveness, not process). The rise of new initiatives with these characteristics has dovetailed with an increase in the funding of international organizations. However, the latter has not necessarily strengthened multilateralism. Instead rapid increases in discretionary earmarked funding to the WHO and World Bank, which we call Trojan multilateralism, has replicated features of the vertical funds. With what consequences for international cooperation? Using principal-agent theory, we find a mixed picture. International organizations are being redirected by specific incentives. However, two constraints on bilateral control are not shifting. There is a persistent asymmetry of information between the WHO or the World Bank and individual member states which gives the former a degree of autonomy. Equally, there are persistent obstacles to tightening bilateral monitoring of multilateral action. We conclude that the positive lessons to be drawn from vertical initiatives need to be balanced by the risks posed from a convergence of vertical initiatives and Trojan multilateralism.
Keywords: 330; Gesundheitsversorgung; Gesundheitspolitik; Internationale Zusammenarbeit; Internationale Organisation; Macht; Asymmetrische Information; Prinzipal-Agent-Theorie; Welt